2019
DOI: 10.36834/cmej.43303
|View full text |Cite
|
Sign up to set email alerts
|

Delivering on the promise of competency based medical education – an institutional approach

Abstract: The Royal College of Physicians and Surgeons of Canada (RCPSC) adopted a plan to transform, over a seven-year horizon (2014-2021), residency education across all specialties to competency-based medical education (CBME) curriculum models. The RCPSC plan recommended implementing a more responsive and accountable training model with four discrete stages of training, explicit, specialty specific entrustable professional activities, with associated milestones, and a programmatic approach to assessment across reside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 6 publications
0
25
0
Order By: Relevance
“…7) This challenge was also identified in the present study, in which residents who were not CC members often had the impression that CCs were a ‘black box’ in terms of their decision‐making processes. Given the importance of stakeholder engagement in ensuring the successful implementation of CBME, 40 it is important that programmes liaise with residents to explain how CCs make decisions and ensure that residents understand the expectations they must fulfil as learners. In addition to improving engagement, this may also help to increase the amount of data available to CCs, as many programmes reported that residents were not initiating assessments as often as required.…”
Section: Discussionmentioning
confidence: 99%
“…7) This challenge was also identified in the present study, in which residents who were not CC members often had the impression that CCs were a ‘black box’ in terms of their decision‐making processes. Given the importance of stakeholder engagement in ensuring the successful implementation of CBME, 40 it is important that programmes liaise with residents to explain how CCs make decisions and ensure that residents understand the expectations they must fulfil as learners. In addition to improving engagement, this may also help to increase the amount of data available to CCs, as many programmes reported that residents were not initiating assessments as often as required.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the initial experience at Queen's University, one of the earlier centres to adopt widespread postgraduate implementation, has highlighted the critical importance of the creation of leadership roles in both faculty, educational leaders and residents to optimize effective implementation by actively co-engaging all stakeholders in the process. 26,32 In the theme value of feedback for residents, study participants reported that they valued specific and actionable feedback. Recent studies reported that qualitative narrative, actionable and specific feedback was of great value and facilitated a conversation with more credibility, allowing the learner to be more at ease.…”
Section: Discussionmentioning
confidence: 99%
“…Assuming that competency is met after a specific number of procedures is very unlikely to capture those who need additional training before commencing independent practice. Competency-based learning, on the other hand, relies on the notion that trainees must demonstrate well-defined educational goals before progressing to the next step of their training [23, 24]. The advantage of competency-based learning is that all trainees will meet the same educational goals, and the only variable that differs between trainees is the time to achieve these goals.…”
Section: Discussionmentioning
confidence: 99%